It’s Not What You Know, It’s…: The Untold Stories of Parent Advocates - Tania Giordani (Adult Education Research Conference, 2007)
After reviewing the literature on parental involvement, it is evident that there is a lack of scholarly information that speaks directly toward parents advocating for all children. This paper explores the common characteristics and motivations of mothers who are advocating for changes within the public school system.